Satis Amplam Libertatem: An Interpretation of Spinoza’S Political Treatise [Satis Amplam Libertatem: Una Interpretación Sobre el Tratado Político de Spinoza] - Sobarzo-Morales, M (Universidad Compultense Madrid, 2019)
Within Spinoza’s mature work Ethics and Theologico-political treatise (TTP) have been thoroughly analyzed. However, Political treatise (TP) has been considered a minor piece for being an unfinished work which contains some structural problems. Despite these flaws, we claim that TP contains Spinoza’s most accomplished political theory since all the consequences of being guided by a strictly immanent notion of politics are drawn in this piece of work. In this sense, TP follows the program outlined by Spinoza’s fundamental doctrine found in Ethics more consistently than TTP does. This leads to the consideration of politics as tendency in two opposite directions: power expansion and power concentration. © 2019 Universidad Complutense de Madrid. All rights reserved.